The antimicrobial properties of exogenous copper in human synovial fluid against Staphylococcus aureus : an in vitro study - Fernando Diaz Dilernia; David Watson; David Heinrichs; Edward Vasarhelyi (Bone & Joint Research)
Aims: The mechanism by which synovial fluid (SF) kills bacteria has not yet been elucidated, and a better understanding is needed. We sought to analyze the antimicrobial properties of exogenous copper in human SF against Staphylococcus aureus. Methods: We performed in vitro growth and viability assays to determine the capability of S. aureus to survive in SF with the addition of 10 µM of copper. We determined the minimum bactericidal concentration of copper (MBC-Cu) and evaluated its sensitivity to killing, comparing wild type (WT) and CopAZB-deficient USA300 strains. Results: UAMS-1 demonstrated a greater sensitivity to SF compared to USA300 WT at 12 hours (p = 0.001) and 24 hours (p = 0.027). UAMS-1 died in statistically significant quantities at 24 hours (p = 0.017), and USA300 WT survived at 24 hours. UAMS-1 was more susceptible to the addition of copper at four (p = 0.001), 12 (p = 0.005), and 24 hours (p = 0.006). We confirmed a high sensitivity to killing with the addition of exogenous copper on both strains at four (p = 0.011), 12 (p = 0.011), and 24 hours (p = 0.011). WT and CopAZB-deficient USA300 strains significantly died in SF, demonstrating a MBC-Cu of 50 µM against USA300 WT (p = 0.011). Conclusion: SF has antimicrobial properties against S. aureus, and UAMS-1 was more sensitive than USA300 WT. Adding 10 µM of copper was highly toxic, confirming its bactericidal effect. We found CopAZB proteins to be involved in copper effluxion by demonstrating the high sensitivity of mutant strains to lower copper concentrations. Thus, we propose CopAZB proteins as potential targets and use exogenous copper as a treatment alternative against S. aureus.